A decade of DNA-hybrid catalysis: from innovation to comprehension. Issue 34 (9th May 2017) - Duchemin, Nicolas; Heath-Apostolopoulos, Isabelle; Smietana, Michael; Arseniyadis, Stellios
Abstract : Since the pioneering work of Roelfes and Feringa in the field of DNA-based asymmetric catalysis, the unique chirality of oligonucleotides has allowed the development of a variety of asymmetric synthetic transformations. This review offers a complete overview of the field. Abstract : In a little over a decade, the unique chirality of oligonucleotides has allowed the development of a variety of asymmetric synthetic transformations. The concept lies in embedding an achiral transition metal catalyst in a DNA double helix, which provides the necessary chiral microenvironment to selectively form one enantiomer of a given reaction product. The most recent efforts at unveiling new reactivities have been accompanied by the desire to understand the mechanisms by which the chirality is transferred and the influence of the interaction between DNA and the metallic co-factor on the selectivity. By offering a complete overview of the field, this review aims to highlight the intricate correlation between the structure of the chiral bio-inorganic scaffold and its catalytic efficacy.